1988
DOI: 10.1080/00288330.1988.9516310
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature variations at coastal sites around New Zealand

Abstract: Sea surface temperature (SST) observations from 16 coastal sites around New Zealand are analysed along with some corresponding air temperatures. Day-to-day variations in SST show weak periodicity over an 8-16 day range. Air temperatures are generally cooler and short-term fluctuations have 3-4 times the standard deviation of the SSTs. Seasonal SST variations are described and coastal SSTs are compared with offshore SST data. At Farewell Spit the coastal SSTs were always cooler than offshore SSTs which supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…7), 1982/83, and 1986/87. This is consistent with the results of Greig et al (1988), who found that El Nifio years were characterised by cooler sea surface temperatures at Leigh and Portobello (on the east coast of the North Island and South Island respectively). The cooler temperatures seem to have no obvious effect on the mixing depths.…”
Section: Model Simulations For the West Coastsupporting
confidence: 82%
See 1 more Smart Citation
“…7), 1982/83, and 1986/87. This is consistent with the results of Greig et al (1988), who found that El Nifio years were characterised by cooler sea surface temperatures at Leigh and Portobello (on the east coast of the North Island and South Island respectively). The cooler temperatures seem to have no obvious effect on the mixing depths.…”
Section: Model Simulations For the West Coastsupporting
confidence: 82%
“…Unfortunately the observations are not sufficient to determine how well these predictions represent the real ocean. Some of the measured interannual variability of coastal temperatures around New Zealand is related to the El Nifio / Southern Oscillation phenomenon (Greig et al 1988), and it is interesting to see whether the modelled mixed layer cycles also show such a teleconnection. A link could occur through the surface forcing, if the weather data from Farewell Spit are correlated with the Southern Oscillation.…”
Section: Model Simulations For the West Coastmentioning
confidence: 99%
“…Also, the use in both surveys of a 1 mm mesh to process the samples rather than a 0.5 mm, or finer, mesh would tend to diminish the contribution of possible seasonal peaks of juveniles to samples. There was, however, a major El Nino event in 1982-83, producing unusually cold sea-surface temperatures in New Zealand coastal waters (Greig et al 1988), and off the South Island west coast (Rahmstorf 1992). Such environmental anomalies might also be expected to favour more opportunistic species.…”
Section: Discussionmentioning
confidence: 99%
“…Superfamily LEPRALIELLOIDEA Vigneaux, 1949 Family LEPRALIELLIDAE Harmer, 1957 Celleporaria agglutinans (Hutton, 1873 (Gordon 1989), in a range of bottom temperatures of c. 8-20°C (Greig et al 1988). …”
Section: Systematicsmentioning
confidence: 99%